2009
DOI: 10.3390/molecules14114414
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Azafluorenone Alkaloids from Polyalthia debilis (Pierre) Finet & Gagnep.

Abstract: This study investigated bioactive extracts of Polyalthia debilis (Annonaceae) with antimicrobial, antimalarial and cytotoxic activities. Extensive chromatographic isolations provided azafluorenone alkaloids; onychine (1) and 7-methoxyonychine (2) together with a mixture of β–sitosterol and stigmasterol. The two alkaloids were isolated from the P. debilis for the first time. Isolated fractions containing a mixture of triterpenoids (C7, C8 and C9) exhibited the most potent antimicrobial activity against many bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…This increased percent suppression of parasitemia with increased dose was observed by other studies on different plant species [15][16][17][18]. Alkaloids, polyphenolic compounds, terpenoids, flavonoids and quercetin in this extract could be responsible for its antimalarial activity [19][20][21][22][23]. Moreover, it has been reported that quercetin and terpenoids showed strong antimalarial, anti-microbials and anti-cancer activities [23].…”
Section: Discussionmentioning
confidence: 50%
“…This increased percent suppression of parasitemia with increased dose was observed by other studies on different plant species [15][16][17][18]. Alkaloids, polyphenolic compounds, terpenoids, flavonoids and quercetin in this extract could be responsible for its antimalarial activity [19][20][21][22][23]. Moreover, it has been reported that quercetin and terpenoids showed strong antimalarial, anti-microbials and anti-cancer activities [23].…”
Section: Discussionmentioning
confidence: 50%
“…The structure is closely related to the dimers of (TMP) 2 Cu(CN)Li 2 ·THF 9 and (TMP) 2 Cu(I)Li 2 ·THF, 10 with Cu maintaining a near linear geometry (N(1)-Cu(1)-N(2) 174.45(11)°) and the amides acting as inter-metal bridges (Cu(1)-N(1)-Li(1) 92.1(2), Cu(1)-N(2)-Li(2) 84.77(19)°). However, in contrast to the cyanide-and iodide-based dimers, in which the THF-solvated Li + ions reside within 0.14 and 0.15 Å, respectively, of planes defined by the (LiX) 2 (X = N, I) metallocyclic cores of the structures, in 1 2 they are significantly displaced (by 0.49 Å) from the analogous (LiCl) 2 core plane. Lastly, we can empirically view formation of the higher-order dimer as resulting from the formal insertion of two units of in situ-generated LiCl·THF 11 into a lower-order dimer based on a (NCuNLi) 2 ring.…”
Section: Resultsmentioning
confidence: 90%
“…Using Cy 3 P in DMF at 130 °C, different transition metal-ligand ratios were tested. The best result was observed using 5 mol% of Pd(OAc) 2 and 10 mol% of phosphine; using 20 mol% of Pd(OAc) 2 and 10 mol% of phosphine, a lower yield was observed due to recovered starting material (Scheme 1). (9) 25 were formed from the ketones 2 and 3b respectively, and isolated in 63-69% yield (Scheme 2).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…(Rhamnaceae) stems gave the highest and lowest yields of 43.88 and 4.97% w/w, respectively. Several traditional uses including cancer treatment of the medicinal plants have been reported (Coe & Anderson, 2005;Houghton et al, 2007;Manaharan et al, 2011;Manosroi et al, 2009;Prachayasittikul et al, 2009;Siriwatanametanon et al, 2010;Su et al, 2008;Trakulsomboon et al, 2006;Ueda et al, 2002).…”
Section: Preparation Of 23 Medicinal Plant Crude Extracts (Mes)mentioning
confidence: 99%